AN ANALYSIS OF STUDENTS’ ERRORS IN WRITING INTRODUCTION OF THESIS OF ENGLISH DEPARTMENT STUDENTS OF IAIN RADEN INTAN - Hidayat, Agus (English Education: Jurnal Tadris Bahasa Inggris, 2015)
The objective of this study is to analyze the grammatical errors in writing introduction (Chapter 1) of thesis of English Department Students of IAIN Raden Intan Lampung . The writer selected in the study because most of English Department students still made mistakes or errors in English. The type of the study used in this case is descriptive qualitative research. This study is done by classifying and analyzing the graduating paper as the objects based on the types of grammatical errors proposed byAzar (1989: A29), they are Singular/Plural error, Verb-Tense Error, Subject-Verb Agreement Error, Verb-Form Error, and Word-Form Error. Based on the data analyzed, it was found that the frequent and dominant errors done by the theses writer are as follow: Singular/Plural Noun Form (19.11%), Verb-Tense Error (23.53%), Verb-Form Error (16.17%),  Subject-Verb Agreement (30.88%) and Word-Form Error (10.29%).